“Between arepas and cazuelas”: daily eating habits of the sons and daughters of Venezuelan migrant mothers in Chile - Castillo, Lucia Odette (2024)
Introduction: The increase in Venezuelan migration, its tendency towards feminization, as well as the number of children and adolescents belonging to Venezuelan migrant families in Chile, invite an intercultural reflection on parenting practices, which involves feeding practices, given their health and social connotation. Methodology: Qualitative supported by the assumptions of symbolic interactionism. Semi-structured interviews were conducted, after signing informed consent, with 19 Venezuelan migrant mothers who met the defined inclusion criteria, between October 2021 and January 2022. The stories were subjected to thematic content analysis. Results: It was theorized around three categories of analysis, namely: identity heritage and integration of Chilean culinary culture, maternal deficiencies and assessment of food availability in Chile and the ambivalent relationship with the Chilean health system. Conclusions: Venezuelan mothers build a personal way of feeding their sons and daughters in Chile, based on the preservation of beliefs and traditions, and also from their experiences linked to the lack experienced in Venezuela, which draw a special appreciation of availability and access to food in the country. On the other hand, the integration of the knowledge learned in its interaction with Chilean society through health establishments is highlighted, which, for some of the participants, harbors tensions linked to the assimilationist practices exercised by the Chilean health system, through the imposition of hegemonic infant feeding practices far from an intercultural approach.